Paralele w semikomunikacji użytkowników języków północnogermańskich i zachodniosłowiańskich - Lipowski, Jaroslav (Slavia Occidentalis, 2012)
Semi-communication as a limited form of verbal communication in the linguistic literature has been taken into consideration, especially in relation to the Danes, Swedes and Norwegians. The author compares some characteristic features of the communication between the Czechs, the Poles and the Slovaks. The author presents some common and a number of distinctive features. For example, there is a different inverse proportion between the comprehension of written and spoken language. A special attention is given to the similarity of the role (contributing element) of social, cultural and political phenomena, compensating differences in language systems communicating with groups of users in multiple languages. In this paper, the author also indicates a creation of a new language as one of the results of the Czech and Slovak communication. The author also incorporates in semi-communication the verbal contact of users of regional dialects and the standard language.